2009
DOI: 10.1007/s00248-009-9598-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Uranium Mining-Impacted Soils as Revealed by High-Density 16S Microarray and Clone Library

Abstract: Microbial diversity was characterized in mining-impacted soils collected from two abandoned uranium mine sites, the Edgemont and the North Cave Hills, South Dakota, using a high-density 16S microarray (PhyloChip) and clone libraries. Characterization of the elemental compositions of soils by X-ray fluorescence spectroscopy revealed higher metal contamination including uranium at the Edgemont than at the North Cave Hills mine site. Microarray data demonstrated extensive phylogenetic diversity in soils and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 46 publications
10
56
2
Order By: Relevance
“…By contrast, no detectable effects on microbial community structure, microbial activity, potential soil N mineralization or nitrification rates were observed at a sweetgum FACE experiment in Tennessee, USA (Austin et al, 2009). For testing our core hypothesis, this study had several strengths: (i) It was conducted at a well-designed BioCON experimental site, with 12 replicates for each CO 2 condition, so that the effects of eCO 2 on soil microbial communities could be robustly examined; (ii) PhyloChip is considered a powerful tool for a comprehensive survey of microbial richness and composition Rastogi et al, 2010), which may overcome the limitations of cloning-based approaches and (iii) this study was conducted in a grassland ecosystem with defined plant species, which minimizes the effects of plant diversity and composition on soil microbial communities. Indeed, consistently with some previous studies in grasslands (Schortemeyer et al, 1996;Drissner et al, 2007), our results indicated that eCO 2 had significant effects on the richness, composition and structure of soil microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, no detectable effects on microbial community structure, microbial activity, potential soil N mineralization or nitrification rates were observed at a sweetgum FACE experiment in Tennessee, USA (Austin et al, 2009). For testing our core hypothesis, this study had several strengths: (i) It was conducted at a well-designed BioCON experimental site, with 12 replicates for each CO 2 condition, so that the effects of eCO 2 on soil microbial communities could be robustly examined; (ii) PhyloChip is considered a powerful tool for a comprehensive survey of microbial richness and composition Rastogi et al, 2010), which may overcome the limitations of cloning-based approaches and (iii) this study was conducted in a grassland ecosystem with defined plant species, which minimizes the effects of plant diversity and composition on soil microbial communities. Indeed, consistently with some previous studies in grasslands (Schortemeyer et al, 1996;Drissner et al, 2007), our results indicated that eCO 2 had significant effects on the richness, composition and structure of soil microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…PhyloChip (G2) consists of 506 944 probe features, and of these features, 297 851 are oligonucleotide perfect match (PM) or mismatch match (MM) probes for 16S rRNA genes (Brodie et al, 2006. PhyloChip has been used to detect microorganisms in a variety of environments, such as contaminated sites (Brodie et al, 2006;Rastogi et al, 2010), air , water (Hery et al, 2010), soil (Cruz-Martinez et al, 2009;DeAngelis et al, 2009;Yergeau et al, 2009;Teixeira et al, 2010), microbial fuel cell (Wrighton et al, 2008) and Huanglongbing pathogen-infected citrus (Sagaram et al, 2009). In addition, several studies demonstrated that PhyloChip could detect many more bacterial taxa as compared with the 16S rRNA gene-based clone library approach La Duc et al, 2009;Rastogi et al, 2010), suggesting that PhyloChip provides more comprehensive surveys of microbial diversity, composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological roles of this phylum remain largely unexplored (35), but its occurrence has been correlated with increased concentrations of chemical elements and nutrients (37). Verrucomicrobia sequences have been recovered from numerous hydrocarbon-, mercury-, uranium-, and pesticide-contaminated environments, suggesting that they are resistant to a number of contaminants, possess metabolic plasticity, and may play a significant role in the decontamination process (14,57,66). Culturable representatives display diverse metabolic characteristics and range from aerobic heterotrophs involved in organic carbon transformations (41,67) to organisms thriving in metal-rich oligotrophic aquatic environments (78).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine if this clustering is the case, future efforts will include isolation of Hg-resistant Verrucomicrobia strains and testing of their resistance to elevated Hg and their ability to transform Hg and MeHg. Given the methanotrophic properties of some phylum members (23,42,43,66), they may also participate in MeHg demethylation in order to use the methyl group as a carbon source via C 1 metabolism. While the organomercurial lysase (merB) is widely known as the methylmercury demethylase, other genes may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…New and emerging methods, such as metagenomics and metaproteomics, which allow for a greater understanding of microbe-metal interactions, many of which were pioneered as a result of academic and U.S. Department of Energy National Laboratory collaborations, have yielded significant insights into subsurface microbial community dynamics and physiological responses within contaminated environments [194][195][196][197][198][199][200][201][202][203][204][205][206]. Additionally, synchrotron X-ray techniques (e.g., XRD, XANES, and EXAFS) have become tools for biogeochemical studies that enhance our understanding of in situ contaminant sequestration.…”
Section: Summary Challenges and Future Directionsmentioning
confidence: 99%